Comparative heat and gas exchange measurements in the Heidelberg Aeolotron, a large annular wind-wave tank - Nagel, Leila; Krall, Kerstin Ellen; Jähne, Bernd (Ocean science, 2015)
Abstract. A comparative study of simultaneous heat and gas exchange measurements was performed in the large annular Heidelberg Air-Sea Interaction Facility, the Aeolotron, under homogeneous water surface conditions. The use of two gas tracers, N2O and C2HF5, resulted not only in gas transfer velocities, but also in the measurement of the Schmidt number exponent n with a precision of ±0.025. The original controlled flux, or active thermographic, technique proposed by Jähne et al. (1989) was applied by heating a large patch at the water surface to measure heat transfer velocities. Heating a large patch, the active thermography technique is laterally homogeneous, and problems of lateral transport effects are avoided. Using the measured Schmidt number exponents, the ratio of the scaled heat transfer velocities to the measured gas transfer velocities is 1.046 ± 0.040, a good agreement within the limits of experimental uncertainties. This indicates the possibility to scale heat transfer velocities measured by active thermography to gas transfer velocities, provided that the Schmidt number exponent is known and that the heated patch is large enough to reach the thermal equilibrium.
Gesehen am 10.08.2020